"A marathon, not a sprint": Canada and South African apartheid, 1987–1990. (March 2020) - Manulak, Daniel
In 2020, Canada does not maintain diplomatic ties with Iran or Saudi Arabia partly owing to their human rights violations—a choice which has eroded its capacity to act meaningfully in these countries. Thirty years ago, the Brian Mulroney government was faced with a similar decision: to sever relations with the white minority regime in South Africa or use its limited but real influence to contribute constructively to an end to apartheid. This article examines how Canada "punched above its weight" on an issue seemingly peripheral to its national interests from 1987 to 1990. It was during these oft-overlooked years—South Africa's "darkest days"—that Canada engaged through multilateral fora, bilaterally, and its embassy to sustain global pressure and attention on apartheid. In so doing, the Mulroney government became a diplomatic battleground between its major allies, Pretoria, and its African Commonwealth partners. Such efforts were not without costs, but Canada's "advanced middling" role helped to bring about a peaceful transition towards majority rule in South Africa and thus holds contemporary lessons for policymakers.